Mendukung Kesejahteraan Sosial pada Karyawan Melalui Pelatihan Masa Persiapan Pensiun Produktif Berbasis Ketahanan Pangan di Lahan Sempit - Indira Oktavianti; Lailatus Sa’adah; Ibrahim Ibrahim (Asosiasi Seni Desain dan Komunikasi Visual Indonesia, 2026)
Almost all formal workers dedicate all their time and energy to their companies during their productive years. As a result, it is very difficult for workers to start other businesses besides their formal jobs. Without the skills and strategies for entrepreneurship, many workers find it difficult to survive when they reach retirement age. From a sustainable human resource management perspective, the retirement preparation period (MPP) is a strategic phase for maintaining the social welfare of employees and taking preventive measures to address post-retirement social issues such as decreased productivity, economic dependence, and individual social roles. For employees who will enter retirement age in the next two years, PT. Sindopex Perotama regularly conducts MPP training. This year, the MPP training was themed “food security to achieve food self-sufficiency in retirement.” PT. Sindopex Perotama collaborated with LS Farm, Trawas Eduwisata Center (TEC), and a team from KH. A. Wahab Hasbullah University (UNWAHA) Jombang as part of the Tridharma community service program. This activity was achieved by applying the results of evaluations from observations of previous activities so that it was on target through proper planning (identifying needs in collaboration with partners), implementing activities, and providing direct assistance at the activity location. This program is expected to bring about social change, such as greater social welfare for employees approaching retirement age, greater economic independence in terms of food, and greater awareness of the role of retirees in maintaining food availability and social harmony in their neighborhoods. In addition, this program demonstrates sustainable human resource management practices in companies that care about the welfare of their employees until they retire.